Radical surgery with total mesorectal excision in patients with T1 rectal cancer - Kulu, Yakup; Müller, Beat P.; Bruckner, Thomas; Gehrig, Tobias; Büchler, Markus W.; Bergmann, Frank; Ulrich, Alexis (Annals of surgical oncology, 2015)
Radical resection with total mesorectal excision (TME) is the accepted standard of care for most rectal cancers. However, T1 rectal cancers may be at low risk for metastases and are therefore treatable with local resection. The aim of our study was to investigate whether the identification of these patients is possible through existing selection criteria.
Published online: 21 October 2014
Gesehen am 02.06.2020